The Experiment and Simulation on Impact Characteristics of AVGAS Spray Based on Impact Phenomenon - Dimas Endrawan Putra; Nasrul Ilminnafik; M Fahrur Rozy Hentihu; Muh. Nurkoyim Kustanto; Danang Yudistiro (Yayasan Sinergi Multidimensi Kreatif, 2024)
Avition gasoline (avgas) is one of the fuels used for combustion of piston-type aircraft engines and uses ignition in the form of spark plugs or internal combustion engines. In recent years, the use of avgas fuel itself is very high used in high- wing light aircraft engines, namely Cessna. avgas spray phenomenon that collides with the cylinder wall may occur during fuel injection, so it will produce a changed radius and spray height, which will affect the mixing of fuel and air, later engine performance and exhaust emissions will also be affected. Therefore, it is important to know and study the spray impact phenomenon in avgas-fueled aircraft engines. This research is a spray experiment with a specified pressure and sprayed on the combustion chamber wall so that the results of the image can be studied coupled with data from experimental research, it can make research from computational fluid dynamics (CFD) simulations, providing valuable insights for future research in this field.